2021
DOI: 10.16899/jcm.878671
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemisinin Üniversite Öğrencilerinde Sağlık Anksiyetesi, Ölüm Kaygısı ve Bedensel Belirtiler Üzerine Etkisi

Abstract: Objective: Coronavirus disease 2019 , which was first identified in Wuhan, China's Hubei province in December 2019, and affected the whole world, although it may seem that it affects the elderly and its comorbid population more seriously, as the data on the disease increased, it was observed that the disease significantly affected young and non-comorbid people as well. The aim of this study is to examine the health anxiety, death anxiety and physical symptoms caused by the pandemic in university students who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The study characteristics are displayed in Table 1. The included studies were published between 2020 and 2021 (Damirchi et al, 2020; Gokdemir et al, 2020; Guner et al, 2021; Kandemir, 2020; Mirhosseini et al, 2021; Rababa et al, 2021; Sanadgol et al, 2020; Shakil et al, 2021; Söğütlü & Göktaş, 2021). The total number of participants in the studies included in the meta-analysis is 4324.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics are displayed in Table 1. The included studies were published between 2020 and 2021 (Damirchi et al, 2020; Gokdemir et al, 2020; Guner et al, 2021; Kandemir, 2020; Mirhosseini et al, 2021; Rababa et al, 2021; Sanadgol et al, 2020; Shakil et al, 2021; Söğütlü & Göktaş, 2021). The total number of participants in the studies included in the meta-analysis is 4324.…”
Section: Resultsmentioning
confidence: 99%
“…However, both this research and our research, contrary to other studies (etc. Söğütlü & Göktaş, 2021 ; Tang et al, 2020 ; Qiu et al, 2020 ; Wang et al, 2020 ), concern students going to counseling centers during the pandemic era, not only the general university students. Contrary to previous results (Erekson et al, 2021 ), most counselors mentioned the same or increased counseling demands compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma has been linked to the male gender, being a member of an ethnic minority, having low education and socioeconomic level, having trouble finding work, being single, separated, or divorced, as well as issues in friendships and social interactions, the severity of the illness, its perceived danger, and drug usage ( Alonso et al, 2009 ; Angermeyer & Matschinger, 2003 ; Van Brakel, 2006 ). On other hand, one more study has found that females tend to perceive more psychological issues such as panic disorder, death anxiety, and Post-traumatic disorder as compared to males ( Georgieva et al, 2021 ; Söğütlü & Göktaş, 2021 ).…”
Section: Discussionmentioning
confidence: 99%